The Impact of Reflective Leadership on Workplace Belongingness: A Gender-Inclusive Analysis Using a Convergent Mixed Methods Approach - Caminong, Joliber M.; Tanpoco, Manuel R.; Morales, Retchell Rublin L.; Pitargue, Kevin S. (Future Science / FSH-PH Publications, 2023)
This paper examines the impact of reflective leadership on workplace belongingness, with a particular focus on gender differences. Through a combined approach of thematic and quantitative analyses, the study explores the factors that contribute to workplace belongingness and investigates potential variations in these factors based on gender. The findings reveal that reflective leadership positively influences workplace belongingness, with employees perceiving higher levels of reflective leadership in their leaders reporting higher levels of belongingness. The study identifies a safe environment, open communication, and challenging beliefs and assumptions as significant components of reflective leadership that impact workplace belongingness. The thematic analysis highlights the importance of psychological safety, effective communication, the value of work and purpose, and openness to change in fostering workplace belongingness. The quantitative analysis further reveals that the relationship between reflective leadership and workplace belongingness is stronger for female employees compared to male employees. The study emphasizes the need to consider gender-specific factors when promoting workplace belongingness, and it suggests strategies for organizations and leaders to create a positive work environment that enhances belongingness. These strategies include fostering a safe and supportive environment, promoting open communication, encouraging critical thinking, and implementing gender-specific initiatives and policies. The findings contribute to the existing literature by shedding light on the complex relationship between reflective leadership, workplace belongingness, and gender. Overall, promoting workplace belongingness contributes to improved employee well-being, satisfaction, engagement, and organizational performance.